PROSEDUR PELEPASAN SEBAGAI AHLI WARIS MELALUI PENETAPAN PENGADILAN - Kurnia, Ida; Fernandha, Rizqy Dini; Goldwen, Filshella (Jurnal Serina Abdimas, 2024)
Not many people know that each heir has the right to choose to accept the inheritance rights or reject them. In the case of refusal or resignation as an heir, it has been guaranteed by law in Article 1057 of the Civil Code. In practice, the resignation as an heir is based on various reasons, the most frequent of which is that the assets are less than the testator's liabilities. Moreover, the heir is no longer part of the Indonesian Citizens, so it is possible to relinquish the inheritance rights attached to the individual through a Court Stipulation. After obtaining a District Court Stipulation related to the relinquishment of inheritance rights, there are legal consequences, namely the release of the individual from the burden of responsibility as an heir and the descendants or children of individuals who relinquish their inheritance rights cannot replace their inheritance position, so the relationship has been cut off. Problems that often occur in Blok Duku Cibubur Village are found that there is a resident who is in debt even though he does not feel indebted to anyone, it turns out that the debt was inherited by one of his parents who has passed away. Based on the problems experienced by the partners, the Extension Team took the initiative to provide legal education counseling to local residents with the aim that if other residents experience these problems, they can act in accordance with applicable legal provisions. ABSTRAK Tak banyak orang tau bahwa setiap ahli waris memiliki hak untuk memilih menerima hak warisan tersebut atau menolaknya. Dalam hal penolakan ataupun pengunduran diri sebagai ahli waris telah dijamin oleh Undang-Undang dalam Pasal 1057 KUHPer. Dalam prakteknya pengunduran diri sebagai ahli waris didasarkan dengan berbagai alasan yang paling sering yaitu harta aktiva lebih sedikit daripada pasiva si pewaris. Terlebih lagi ahli waris bukan lagi bagian dari Warga Negara Indonesia, sehingga dimungkinkan untuk melepaskan hak waris yang melekat pada individu melalui Penetapan Pengadilan. Setelah mendapatkan Penetapan Pengadilan Negeri terkait terlepasnya hak waris, maka terdapat akibat hukum yang ditimbulkan yaitu terbebasnya individu tersebut dari beban tanggung jawab sebagai ahli waris serta keturunan atau anak-anak dari individu yang melepaskan hak warisnya tidak dapat menggantikan kedudukan warisnya, jadi telah terputus hubungan. Permasalahan yang acap kali terjadi di Desa Blok Duku Cibubur ditemukan bahwa terdapat seorang warga yang terlilit hutang padahal ia tidak merasa berhutang kepada siapapun ternyata hutang tersebut diwariskan oleh salah satu orang tua nya yang telah meninggal dunia. Berdasarkan permasalahan yang dialami oleh mitra Tim Penyuluh berinisiatif untuk memberikan penyuluhan edukasi hukum kepada warga sekitar dengan tujuan apabila warga lain mengalami masalah tersebut, maka dapat bertindak sesuai dengan ketentuan hukum yang berlaku.